As sonatas para violoncelo e piano de M.C. Guarnieri, em contexto: aspectos técnico-interpretativos da Sonata N.3 - Cinthia Fernandes Matias (2021)
The objective of this work is to present a study of the composer Mozart Camargo Guarnieri’s Sonatas for cello and piano, as well as proposing suggestions that enphasize the expressive content of the Sonata N.3. As a foundation for this study, Guarnieri’s evolution as a composer is considered and his three cello sonatas are related to his three compositional phases. Furthermore, private classes were held with cellist Antonio Lauro Del Claro, to whom Sonata N.3 was dedicated and who was present in the realization of Guarnieri’s sonatas for cello and piano. These classes with Del Claro were used to reflect on and record the composer’s intentions and inspirations, as described in the cellist’s memories of their shared experiences throughout the process of creating the sonatas. Biographical sources are used to trace the influences that were important to the compositional process of the work. Finally, this study proposes to support a performance that is coherent with the composer’s intentions.